2020
DOI: 10.1101/2020.12.01.20241562
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Real-life evaluation of a rapid antigen test (Panbio™ COVID-19 Ag Rapid Test Device) for SARS-CoV-2 detection in asymptomatic close contacts of COVID-19 patients

Abstract: Objectives: There is limited information on the performance of rapid antigen detection (RAD) tests to identify SARS-CoV-2-infected asymptomatic individuals. In this field study, we evaluated the Panbio COVID-19 Ag Rapid Test Device (Abbott Diagnostics, Jena, Germany) for the purpose. Methods: A total of 634 individuals (355 female; median age, 37 years; range, 9-87) were enrolled. Household (n=338) contacts were tested at a median of 2 days (range, 1-7) after diagnosis of the index case and non-household con… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
23
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 9 publications
4
23
0
4
Order By: Relevance
“…According to our data, the CLINITEST Ⓡ Rapid COVID-19 Antigen Test meets the criteria recommended in WHO interim guidance for RAD diagnosis of SARS-CoV-2 infection (at least 80% sensitivity and 97% specificity), 7 but as with other commercially-available RAD assays, 4 , 8 , 9 this only applies in symptomatic patients with suspected COVID-19 who are tested shortly after symptoms onset (up to 5 days in the current study). In contrast, the POC performance of this and other RAD assays, 4 , 9 is clearly suboptimal in asymptomatic close-contact individuals, either household or non-household.…”
mentioning
confidence: 63%
See 1 more Smart Citation
“…According to our data, the CLINITEST Ⓡ Rapid COVID-19 Antigen Test meets the criteria recommended in WHO interim guidance for RAD diagnosis of SARS-CoV-2 infection (at least 80% sensitivity and 97% specificity), 7 but as with other commercially-available RAD assays, 4 , 8 , 9 this only applies in symptomatic patients with suspected COVID-19 who are tested shortly after symptoms onset (up to 5 days in the current study). In contrast, the POC performance of this and other RAD assays, 4 , 9 is clearly suboptimal in asymptomatic close-contact individuals, either household or non-household.…”
mentioning
confidence: 63%
“…According to our data, the CLINITEST Ⓡ Rapid COVID-19 Antigen Test meets the criteria recommended in WHO interim guidance for RAD diagnosis of SARS-CoV-2 infection (at least 80% sensitivity and 97% specificity), 7 but as with other commercially-available RAD assays, 4 , 8 , 9 this only applies in symptomatic patients with suspected COVID-19 who are tested shortly after symptoms onset (up to 5 days in the current study). In contrast, the POC performance of this and other RAD assays, 4 , 9 is clearly suboptimal in asymptomatic close-contact individuals, either household or non-household. Two non-mutually exclusive factors may account for this observation: (i) SARS-CoV-2 RNA shedding in the upper respiratory tract (URT) could follow different kinetics in symptomatic and asymptomatic subjects, implying that the sampling time in the latter may have been inappropriate (too early or too late) to capture all infection cases; (ii) SARS-CoV-2 infected individuals not subsequently developing COVID-19 display lower overall viral loads in URT than those who do.…”
mentioning
confidence: 63%
“…Several jurisdictions use the Panbio Ag Rapid Test Device to identify positives early, assuming that negative results should be confirmed [ [34] , [35] , [36] ]. One recent study showed that none of those who were test discordant (positive by RT-PCR but negative using Panbio) had culturable virus in their sample [ 34 ], indicating potentially reduced transmissibility by individuals defined as “false negatives” in current protocols. Other studies have indicated that sensitivity of the Panbio devices drops in people with no symptoms [ 36 ], or when using self-collected specimens such as nasal swabs and saliva [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“… Method Sample type 1 Cost Complexity Scalability Sensitivity Refs. Viral culture NP in VTM Expensive Complex Not scalable Culturable when Ct <24 [ 31 ] RT-PCR (central lab protocols) Extracted NP Expensive Complex Kits, tubes and tips Comparator [ 45 ] Cepheid GeneXpert NP in VTM Expensive Simple Platform and single-use cartridges 95-100% [ 11 , 21 ] Abbott ID NOW Direct NP Expensive Simple Platform and single-use cartridges 70-90% [ 45 , 46 ] Abbott Panbio Ag Direct NP Cheap Simple Single-use cartridges 75-85% [ 34 , 47 , 48 ] NEB RT-LAMP Extract-free NP Cheap Simple Kit, tubes and tips 75-95% [ 23 ] 1...…”
Section: Discussionmentioning
confidence: 99%
“…Data in several reports suggest that such tests may miss presymptomatic and asymptomatic individuals early in the infection. 12,17 However, logical arguments have also been made, 18,19 in favor of widely deploying surveillance tests with "analytic sensitivities vastly inferior to those of benchmark tests." 18 Low-sensitivity tests will be equally effective to high-sensitivity tests at minimizing transmission if the following two assumptions about the early phase of SARS-CoV-2 infection hold true: (i) viral load increases rapidly, by orders of magnitude within hours, and (ii) viral load reaches and sustains high levels during the infectious window, such that a rapid low-sensitivity test would have a similar ability to detect early-phase infections compared with high-sensitivity tests.…”
Section: Introductionmentioning
confidence: 99%